Alcohol Drinking Pattern and Risk of Head and Neck Cancer: A Nationwide Cohort Study - Hye Yeon Koo (MDPI AG, 2021)
Alcohol consumption is a major risk factor for head and neck cancer (HNC), yet little data exist examining drinking patterns and HNC risk. In this population-based, retrospective cohort study, 11,737,467 subjects were recruited from the Korean National Health Insurance Service database. The risks of overall HNC and HNC subtypes according to average alcohol consumption, drinking frequency, and daily amount were examined using Cox proportional hazard models. Over the median follow-up of 6.4 years, 15,832 HNC cases were identified. HNC risk linearly increased with drinking frequency (p-trend < 0.01; adjusted hazard ratio [aHR] 1.55, 95% confidence interval [CI] 1.45–1.67 in subjects who drank 7 days/week). HNC risk also increased according to daily amount of alcohol consumption (p-trend < 0.01), but plateaued from 5–7 units/occasion (aHR 1.25, 95% CI 1.19–1.31) to >14 units/occasion (aHR 1.26, 95% CI 1.13–1.40). When stratified by average alcohol consumption, drinking frequency, but not daily amount, showed a linear relationship with HNC risk in moderate and heavy drinkers. When comparing the HNC subtypes, similar tendencies were observed in cancers of the oral cavity, pharynx, and larynx, but not in the salivary gland. In conclusion, drinking frequency is a stronger risk factor for HNC, especially for cancer of the oral cavity, pharynx, and larynx, than the daily amount of alcohol consumption.